Disability, health, law, & bioethics - Cohen, I. Glenn; Shachar, Carmel 1985-; Silvers, Anita; Stein, Michael Ashley (Cambridge University Press, 2020)
Historically and across societies people with disabilities have been stigmatized and excluded from social opportunities on a variety of culturally specific grounds. In this collection, the authors explore the impact that the philosophical framing of disability can have on public policy questions, in the clinic, in the courtroom, and elsewhere. They examine the implications of this understanding for legal and policy approaches to disability, strategies for allocating and accessing health care, the implementation of the Americans with Disabilities Act, health care rights, and other legal tools designed to address discrimination. This volume should be read by anyone seeking a balanced view of disability and an understanding of the connection between the framing of disability and policies that have a real-world impact on individuals.